Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Intensitas Turnover Karyawan - Widyantara, Ida Bagus Putra; Ardana, I Komang (E-Jurnal Manajemen; Vol 4 No 6 (2015), 2015)
The purpose of this study was to mengethau influence job satisfaction and organizational commitment on employee turnover intensity in the front office department in Kuta Paradisso. This research was carried out at the front office department employees Kuta Paradisso sample size taken by 75 employees of the front office department Hotel Kuta Paradisso. The sampling technique that is saturated sampling census technique, where respondents are taken are all employees of the front office department Hotel Kuta Paradisso. Data was collected through questionnaires that using 5-point Likert scale to measure the 26 items statements. The analysis technique used is multiple linear regression analysis. The results showed that the effect of job satisfaction and organizational commitment simultaneously significant effect on the intensity of the turnover. Second, that job satisfaction is a significant negative effect on the intensity of the turnover. Third, organizational commitment and significant negative effect on the intensity of the turnover.
Keywords: kepuasan kerja; komitmen organisasi; intensitas turnover